Patient Identification Nursing Error - Ardianto Ardianto; Siti Saidah Nasution; Mula Tarigan (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Patient safety goals consist of six safety goals, one of which is the identification process. Where the patient identification process must be carried out correctly so that errors or nursing errors do not occur. The purpose of this study was to determine the relationship between the implementation of patient identification and nursing errors. This research uses associative research with a cross-research design. The sample in this study amounted to 120 people, at the Regional General Hospital Dr. RM. Djoelham Binjai used a total sampling technique. The data collection instrument was used a questionnaire. The results of the study showed that as many as 51 people (96,1%) did not carry out patient identification with a high incidence of nursing errors. Meanwhile, among nurses who carried out patient identification, there was 1 out of 68 people (1,4%) with a high incidence of nursing errors. Based on the results of data processing, it was concluded that the effect of carrying out patient identification was strong by r square=0,911, meaning that the patient identification implementation variable was used in the study. It has been able to explain the diversity of data on nursing error variables at the Regional General Hospital Dr. RM. Djoelham Binjai is 91,1%, while the remaining 8,9% is explained by other variables outside the research model.